Pengaruh Pendapatan dan Gaya Hidup Terhadap Pola Konsumsi pada Masyarakat Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Inda Tri Listri; Supardi Mursalin; Citra Liza (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this study is to find out whether income and lifestyle have an effect on the consumption patterns of the community in Pino Raya District, South Bengkulu Regency, both partially and simultaneously. The method used in this study is quantitative. The sample consisted of 100 respondents selected using the Slovin formula. To determine the accuracy and validity of the instrument, validity and reliability tests were conducted. Data analysis techniques in this study included classical assumption tests, hypothesis testing, and multiple linear regression analysis. Data were processed using SPSS version 26. The results showed that partially, income has a significant effect on consumption patterns with a significance value of 0.027 < 0.05, and lifestyle also has a significant effect with a significance value of 0.000 < 0.05. Simultaneously, income and lifestyle together have a significant effect on consumption patterns with a significance value of 0.000 < 0.05.